The American foreign policy: the peripeteias of relations with the most ancient strategic partner France - Oksana Mitrofanova (Американська історія і політика, 2016)
The peripeteias of relations of two powerful nuclear countries: the hyperpower USA and the European power France significantly define the world politics. The partnership between two states in the context of their influence on the world arena is studied, the shared values of two countries and their reactions to terrorist attacks is highlighted. Anti-Americanism in France and francophobia in the United States are also analyzed.